2012
DOI: 10.1021/la3004323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Subsurface Composition of a Material on the Adhesion of Staphylococci

Abstract: Controlling the interface between bacteria and solid materials has become an important task in biomedical science. For a fundamental and comprehensive understanding of adhesion it is necessary to seek quantitative information about the involved interactions. Most studies concentrate on the modification of the surface (chemical composition, hydrophobicity, or topography) neglecting, however, the influence of the bulk material, which always contributes to the overall interaction via van der Waals forces. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 66%
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 66%
“…44 Recent studies discovered that the influence of the subsurface material on adhesion is sensed by larger biological objects, too: The unspecific adhesion of bacteria from the Staphylococcus genus is affected by the properties of the subsurface material, as could be shown by AFM force spectroscopy measurements. 45 Moreover, adhesion experiments with setal arrays of live geckos revealed that the adhesion force was significantly varied by a change in the substrates subsurface composition. 46 …”
Section: Interactions In Biological Systemsmentioning
confidence: 99%
“…In general, the adhesion of bacteria to a surface is determined by the nature of the bacterium, the surrounding medium, the surface chemistry, and the material composition reflecting the influence of the main interacting forces [1213]: van der Waals forces, hydrophobic interaction and electrostatic forces. In addition, specific interactions amplify bacterial adhesion whenever corresponding binding partners are available.…”
Section: Introductionmentioning
confidence: 99%